The role of social determinant of health in couples' infertility - Elaheh Baybordi (Shahid Beheshti University of Medical Sciences, 2019)
Introduction: Infertility is a medical and social status that can cause social, emotional and psychological disturbances in infertile couples. Although couples are often expected to have child, there are a significant number of infertile people who may be subject to social, economic, physical and psychological effects.  Materials and Methods: This descriptive cross-sectional study was carried out in an interval of 6 months. The participants in this study were infertile couples referring to Tabriz Jahade Daneshgahi Infertility Treatment Center, which is one of the referral centers for infertility treatment in northwestern Iran and they were enrolled in the study after obtaining informed consent. Infertility problems of all participants were diagnosed by numerous physicians and referred to the center for infertility treatment. Self-administered questionnaire with closed questions was provided to the participants using Likert scale to collect data. The questionnaire included demographic data including age, sex, occupation, place of living, income, history of the cause and duration of infertility and social protection of individuals. Results:The total number of participants was 205, with a mean age of 6.89 ±33.78 years. 142 of (69.3%) the participants were female and 63 (30.7%) were male. The mean age of females was 6.73 ± 33.11 and the mean age of males' was7.06 ±35.41 years. In examining the cause of infertility, in which 169 people responded, 66 (39.1%) had male infertility, 48 (28.4%) had female infertility, 54 (32%) had both female and male, and one case (0.6%) with unknown cause.All those with the lowest degree of satisfaction with social facilities and statuses belong to the lowest income group of the community, whereas the degree was moderate to high for the middle-income group. Discussion: An important economic factor is the income of young men links to their parents' income and identifies their ability to support their own families. Low income level has been associated with reduced fertility rates.The number of infertile people who came to receive fertility treatments with income level of below the moderate was 66.3%. And in the lowest income levels, male infertility was significantly different from other causes, which can be said that poverty and low socioeconomic level were more effective in male infertility.Depending on the cultural status and the belief in family unity in the country, the level of social support was high among the participants, and those who had higher levels of income had more social support and more unity with family and friends. Conclusion: Social factors influencing health have greatly influenced the incidence and cause of couples' infertility who want to have a child and have a background for individual's health problems.